2013
DOI: 10.1017/s1368980013001122
|View full text |Cite
|
Sign up to set email alerts
|

Use of vitamin D supplements during infancy in an international feeding trial

Abstract: Objective To examine the use of vitamin D supplements during infancy among the participants in an international infant feeding trial. Design Longitudinal study. Setting Information about vitamin D supplementation was collected through a validated FFQ at the age of 2 weeks and monthly between the ages of 1 month and 6 months. Subjects Infants (n 2159) with a biological family member affected by type 1 diabetes and with increased human leucocyte antigen-conferred susceptibility to type 1 diabetes from twel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Six of the papers in this issue focus on children and adolescents ( 2 , 3 , 6 , 11 , 19 , 24 ) . Black and co-workers ( 19 ) studied vitamin D intakes in a group of children and a group of teens in Ireland who had participated in the Children's and Teens’ National Nutrition Surveys in 2004 and 2007.…”
Section: Vitamin D Status In Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the papers in this issue focus on children and adolescents ( 2 , 3 , 6 , 11 , 19 , 24 ) . Black and co-workers ( 19 ) studied vitamin D intakes in a group of children and a group of teens in Ireland who had participated in the Children's and Teens’ National Nutrition Surveys in 2004 and 2007.…”
Section: Vitamin D Status In Children and Adolescentsmentioning
confidence: 99%
“…Vitamin D supplements have been recommended to children aged 0-2 years in Northern Europe for decades to combat rickets (5) . Lehtonen et al (24) conducted a survey on the use of supplements in 2159 infants aged 1-6 months in Europe, North America and Australia based on data from the TRIGR study -a longitudinal study examining the effect of infant weaning on to a hydrolysed infant formula on incidence of type I diabetes in those with increased genetic susceptibility. Their results revealed that the majority of the infants were supplemented in Europe, approximately half in Canada, yet very few in the USA and Australia.…”
Section: Vitamin D Status In Children and Adolescentsmentioning
confidence: 99%
“…Therefore, the AAP (Wagner, 2008) and the National Academy of Medicine (formerly, Institute of Medicine, 2011) recommend that all breastfed infants and formula-fed infants receiving less than 1 liter of formula per day receive supplementation with 400 IU of vitamin D daily (Institute of Medicine, 2011; Wagner et al, 2008). However, compliance with this recommendation is quite poor in the United States, with studies showing < 2% of all infants receiving vitamin D supplementation (Lehtonen et al, 2014). Recent studies have found that maternal supplementation (4,000-6,400 IU daily or 150,000 IU monthly) is a safe and effective way of achieving vitamin D sufficiency for exclusively breastfeeding infants (Hollis et al, 2015; Oberhelman et al, 2013; Thiele, Senti, & Anderson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…D supplementation (Lehtonen et al, 2014). Recent studies have found that maternal supplementation (4,000-6,400 IU daily or 150,000 IU monthly) is a safe and effective way of achieving vitamin D sufficiency for exclusively breastfeeding infants (Hollis et al, 2015;Oberhelman et al, 2013;Thiele, Senti, & Anderson, 2013).…”
mentioning
confidence: 99%
“…Most of case-control studies have pointed out that lower intake of vitamin D during early life is associated with higher risk of type 1 diabetes, and a meta-analysis including studies published up to 2011 [7] has estimated a pooled odds ratio (OR) of 0.71 (95 % CI 0.51-0.98) for vitamin D supplementation with respect to non-supplementation. Results, however, might have been hampered by misclassification of vitamin D intake, generally assessed through questionnaires [8]. Managed Heterogeneities among studies might be due to differences among populations in levels of solar ultraviolet B radiation at different latitudes, dietary supplementation, genetic factors and age of examined people.…”
Section: Introductionmentioning
confidence: 99%